Rodinný dům s provozovnou - Klimeš, Adam (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Předmětem bakalářské práce je projektová dokumentace rodinného domu s provozovnou umístěný v Brně, Soběšice. Tvarové řešení domu je navrženo do tvaru L. Dům je dvoj podlažní a podsklepený. Dům je rozdělen na dvě části a to na obytnou část a kancelář. Do budovy vedou dva hlavní vstupy vedoucí do obytné části a provozovny a dva vedlejší. Konstrukční systém objektu je navržen jako stěnový. Dům je založen na základových pasech. Střešní konstrukce je navržena jako plochá střecha a střecha nad obývacím pokojem je navržena jako vegetační střecha.

The subject of the bachelor's thesis is the project documentation of a family house with an establishment located in Brno, Soběšice. The shape of the house is designed in an L-shape. The house has two floors and a basement. The house is divided into two parts: a residential area and an office. There are two main entrances leading to the residential part and the establishment, and two side entrances. The structural system of the building is designed as a wall system. The house is founded on strip foundations. The roof structure is designed as a flat roof, and the roof above the living room is designed as a green roof.
Family House with Workshop
Keywords: Bakalářská práce; rodinný dům; provozovna; pórobetonové tvárnice; základové pasy; plochá střecha; vegetační střecha; skládaná stropní konstrukce; Bachelor's thesis; family house; establishment; aerated concrete blocks; strip foundations; flat roof; green roof; prefabricated ceiling structure